The dangers of iodine-based contrasts in an elderly patient with thyroid disease. (24th March 2015) - Ledingham, David; Carey, Peter; Junejo, Shahid
Abstract : Iodine-based contrast agents are widely used in angiographic and other radiological procedures. Clinicians are familiar with many of the potential adverse events from contrast agents including allergic reactions and contrast-induced nephropathy. This case describes a lesser known adverse event: 'contrast-induced thyrotoxicosis' and its implications on the presentation and management of a patient with severe coronary artery disease. The management of this case was difficult and required a long inpatient admission with use of prednisolone, propylthiouracil and planned treatment with radioiodine to control the thyrotoxicosis, as well as the use of several rate-limiting agents and antianginal medications to control atrial fibrillation and prevent further episodes of angina.